The children's story in the development of mathematical concepts - Postijo Remache, Felix (2009)
The research was conducted to determine the effect of children's stories to promote the development of mathematical concepts in children from first grade of elementary education from the College National Implementation UNHEVAL. To this end, 15 children were selected as sample and, at the beginning of the implementation of research work, answered a pretest consisting of a test on notions of mathematical concepts such as: Notions space, the time, space, and quantification numerals, in order to determine the knowledge of these concepts and as children began Then proceeded to develop activities, which lasted one month, and at the end of which they were returned to implement the post, consisting of the same test. The results to which we arrived showed that the implementation of children's stories is better for the development of mathematical concepts in children from first grade of elementary education.